SeamDock: An Interactive and Collaborative Online Docking Resource to Assist Small Compound Molecular Docking - Murail, Samuel; de Vries, Sjoerd J.; Rey, Julien; Moroy, Gautier; Tufféry, Pierre (Frontiers in Molecular Biosciences, 2021)
In silico assessment of protein receptor interactions with small ligands is now part of the standard pipeline for drug discovery, and numerous tools and protocols have been developed for this purpose. With the SeamDock web server, we propose a new approach to facilitate access to small-molecule docking for non-specialists including students. The SeamDock online service integrates different docking tools in a common framework that allows ligand global and/or local docking and a hierarchical approach combining the two for easy interaction site identification. This service does not require advanced computer knowledge and it works without the installation of any programs with the exception of a common web browser. The use of the seamless library linking the RPBS calculation server to the user's web page, allows the user to navigate smoothly and interactively on the SeamDock web page. A major effort has been put into the 3D visualization of ligand, receptor, and docking poses and their interactions with the receptor. The advanced visualization features combined with the seamless library allow a user to share with an unlimited number of collaborators, a docking session, and its full visualization states. As a result, SeamDock can be seen as a free, simple, didactic, evolving online docking resource best suited for education and training.